IMPLEMENTATION OF FISH DISTRIBUTION QUALITY WITH COLD CHAIN SYSTEM (CASE STUDY: PRIGI TO TULUNGAGUNG) - Sa'adah, Nor; Maisaroh, Dian Sari; Sukma, Raka Nur; Aji, Prasetyo Bayu (Department of Marine Engineering, Universitas Hang Tuah, 2024)
Prigi Nusantara Fishing Port is a port located in the south of Java Island. Where the production of fishermen's catches that can be landed at the Prigi Nusantara Fishing Port is 24,928,229 kg. It is necessary to have a management plan and identification of cold chain system distribution costs to maximize the distribution of catches, in this study to the Tulungagung area. Cold storage also has an important role in the cold chain system. Thus, this study plans to identify the management process identify distribution costs, and assess the role of cold storage. This research aims to identify the management process and identify distribution costs as well as assess the role of cold storage. The results of this management mapping plan are from fishermen to cold storage, cold storage processing, and transportation to markets and consumers. With a total cost of IDR 173,382,000/year, including operational costs of IDR 82,950,000/year and vehicle travel costs of IDR 90,43,000/year, using a Thermo King truck. Assessment of the role of government cold storage obtained a score of 45.8% while private cold storage 43.6%. The role of cold storage is still not optimal for storing fish to stabilize prices.